Prognostic Significance of Immunohistochemical Expression of EGFR and C-erbB-2 Oncoprotein in Curatively Resected Gastric Cancer - Song, Hong Suk (Korean Cancer Association, 2004)
PURPOSE: The purpose of this study was to investigate the prognostic significance of the expression of EGFR and C-erbB-2 gene products by immunohistochemical analysis for curatively resected gastric adenocarcinoma. MATERIALS AND METHODS: Between January 1996 and December 2001, 739 patients with curatively resected gastric cancer patients underwent immunohistochemical staining for EGFR and C-erbB-2 proteins, and we retrospectively analyzed their correlation with the clinical outcome. RESULTS: The overexpressions of EGFR and C-erbB-2 were 25.4% and 26.2%, respectively. The overexpressions of EGFR was associated with the more poorly differentiated tumor (p=0.000) and with neuronal invasion (p=0.03). Overexpression of C-erbB-2 was associated with less vascular invasion (p=0.001). Tumor depth or node metastasis was not related to the overexpression of EGFR or C-erbB-2. The seven-year overall survival and relapse-free survival rates were 87.2% and 75.8%, respectively. Upon multivariate Cox regression analysis, the tumor stage, tumor size and patient age were important prognostic factors for overall survival, and tumor stage was the important factor for relapse-free survival. Overexpressions of EGFR or c-erbB-2 were not significant prognostic factors. CONCLUSION: Immunohistochemical staining of EGFR and C-erbB-2 gene products were not independent prognostic factors for predicting the overall survival and the relapse-free survival in curatively resected gastric cancer.